Impact of the COVID-19 pandemic on the outcome, morbidity, and mortality of acute care surgery patients: A retrospective cohort study - Chonlada Krutsri (2022)
Background: Coronavirus disease (COVID-19) has impacted both emergency and elective surgical management owing to its highly infectious nature and the shortage of personal protective equipment. This study aimed to review the outcomes of emergency surgical conditions and trauma during the pandemic lockdown. Material and methods: We retrospectively reviewed and collected data from patients who attended the Acute Care Surgery Service from 1st April to May 31st, 2020 during Thailand's COVID-19 pandemic lockdown. We separated staff and performed preoperative COVID-19 swab testing on all patients to assess the requirement for personal protective equipment. Compared with previous years of service, of 2018 and 2019. Preoperative COVID-19 testing was performed using multiplex and manual RT-PCR. Morbidity and mortality, consultation time, and waiting time to surgery were analyzed. Results: A total of 61 patients were enrolled. The average age of patients was 53.8 years. The average consultation time, waiting time to surgery, and surgical duration were 10 min, 660 min, and 88.77 min, respectively. The average time taken to obtain the preoperative COVID-19 test result was 227.26 min. The morbidity and mortality rates were 9.84% and 1.64%, respectively. Compared with the same period in 2018 and 2019, consultation time was significantly faster (10 min; p = 0.033) and waiting time to surgery was significantly longer (660 min, respectively; p = 0.011). Morbidity and mortality between pandemic period and the previous year of service were not significantly different. No medical workers were infected with COVID-19. Conclusions: During the COVID-19 pandemic, optimal triage of emergency patients is key. Waiting for preoperative COVID-19 swab testing in emergency case is safe and results in good outcomes. Although the waiting time to surgery was significantly longer owing to the time required to receive preoperative COVID-19 swab results, morbidity and mortality rates were unaffected.